Olive oil abrogates acrylamide induced nephrotoxicity by modulating biochemical and histological changes in rats. (1st January 2017) - Ghorbel, Imen; Elwej, Awatef; Fendri, Nesrine; Mnif, Héla; Jamoussi, Kamel; Boudawara, Tahia; Grati Kamoun, Naziha; Zeghal, Najiba
Abstract: Acrylamide (ACR) is one of the most important contaminants occurring in foods heated at high temperatures. The aim of this study is to investigate the protective efficacy of extra virgin olive oil (EVOO), a main component of the Mediterranean diet, against nephrotoxicity induced by ACR. Rats have received by gavage during 21 days either ACR (40 mg/kg body weight) or ACR-associated with EVOO (300 μl) or only EVOO (300 μl). Acrylamide induced nephrotoxicity as evidenced by an increase in malondialdehyde (MDA), hydrogen peroxide (H2 O2 ), protein carbonyls (PCOs) and a decrease in glutathione, non-protein thiols (NPSHs), and vitamin C levels. Activities of catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GPx) were also decreased. Lactate dehydrogenase (LDH) activity, creatinine, urea, and uric acid, urinary volume and creatinine clearance levels were modified. EVOO supplementation improved all the parameters indicated above. Kidney histoarchitecture confirmed the biochemical parameters and the beneficial role of EVOO. EVOO, when added to the diet, may have a beneficial role against kidney injury by scavenging free radicals and by its potent antioxidant power.